2005
DOI: 10.1016/j.yexcr.2005.03.026
|View full text |Cite
|
Sign up to set email alerts
|

Antisense inhibition of hyaluronan synthase-2 in human osteosarcoma cells inhibits hyaluronan retention and tumorigenicity

Abstract: Osteosarcoma is a common malignant bone tumor associated with childhood and adolescence. The results of numerous studies have suggested that hyaluronan plays an important role in regulating the aggressive behavior of various types of cancer cells. However, no studies have addressed hyaluronan with respect to osteosarcomas. In this investigation, the mRNA expression copy number of three mammalian hyaluronan synthases (HAS) was determined using competitive RT-PCR in the osteoblastic osteosarcoma cell line, MG-63… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
63
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 33 publications
(31 reference statements)
8
63
0
1
Order By: Relevance
“…Treatment of these cells with exogenous high-molecular weight HA showed a similar increase in cell motility. Exogenous HA was recently reported to stimulate osteosarcoma cell migration in support of our data (18). In the present study and in agreement with previous (18), downregulation of HAS2 expression by siRNA inhibited MG-63 cell ability to migrate.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Treatment of these cells with exogenous high-molecular weight HA showed a similar increase in cell motility. Exogenous HA was recently reported to stimulate osteosarcoma cell migration in support of our data (18). In the present study and in agreement with previous (18), downregulation of HAS2 expression by siRNA inhibited MG-63 cell ability to migrate.…”
Section: Discussionsupporting
confidence: 94%
“…Exogenous HA was recently reported to stimulate osteosarcoma cell migration in support of our data (18). In the present study and in agreement with previous (18), downregulation of HAS2 expression by siRNA inhibited MG-63 cell ability to migrate. The addition of PTH (1-34) to HAS2-defficient osteosarcoma cells did not stimulate their migration, suggesting that HAS2-synthesized HA participates in the PTH (1-34) effect.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Therefore, HAS2, which synthesizes an extremely large HA (average >2x10 6 Da), may play a crucial role in the formation of the pericellular coat. A recent study reported that formation of the pericellular coat, on osteosarcoma cell line MG63, was suppressed by treatment with HAS2 antisense oligonucleotides (47). This finding does not conflict with the findings of our study.…”
Section: Discussionsupporting
confidence: 79%
“…Knockdown of the HAS genes in tumor cells was reported to inhibit their proliferation, invasion and motility in vitro and tumor growth and metastasis in vivo (16)(17)(18)(19)(20)(21)(22). In particular, it has been reported that the levels of HAS2 expression are often correlated with malignant behavior in various cancer cells such as breast cancer, fibrosarcoma and osteosarcoma cells (17,(23)(24)(25). Furthermore, HAS2 is a key molecule for the induction of the epithelial-mesenchymal transition (EMT) with HA assembly (26)(27)(28)(29)(30).…”
Section: Introductionmentioning
confidence: 99%